Kajian Literatur: Penanganan Psikologis Pada Remaja Dengan Bullying Menggunakan Cognitive Behaviour Therapy - Wulan, Winda Ratna (Jurnal Keperawatan Komplementer Holistic, 2025)
Bullying is a form of violent behavior characterized by psychological or physical coercion against an individual or a group of individuals who are perceived as "weaker" by another individual or group. Behavioral therapy is an approach to counseling and psychotherapy that focuses on changing behavior. The aim of this research is to determine the effectiveness of Cognitive Behavioral Therapy (CBT) in addressing psychological issues in adolescents affected by bullying, the steps involved in CBT, and the characteristics of the sample taken. The sources for this literature review were obtained through "Google Scholar." The writing method used is a journal-based literature review, which involves several stages: determining a broad topic, screening journals, and identifying themes from the references obtained. The results of the literature review indicate that the application of CBT is effective in addressing psychological issues in adolescents affected by bullying, leading to increased self-esteem and confidence in bullying victims, reduced anxiety in facing bullying behavior, and a decrease in aggressive behavior among bullying perpetrators.